Doing the possible: harm reduction, injecting drug use and blood borne viral infections in Australia - Loxley, Wendy (2000)
Most surveys show that, other than among men who inject drugs and have a history of homosexual contact, the prevalence of HIV infection among injecting drug users (IDUs) in Australia is about 2%. Rates of needle sharing have also declined greatly in the last decade, although the high prevalence and incidence of hepatitis C infection suggest that existing strategies have not yet brought this epidemic under control. Harm reduction has been the major Australian approach to the reduction of blood borne viral infections (BBVIs) in IDUs. Harm reduction strategies include needle distribution schemes, drug substitution therapies and education about safe administration practices. Importantly, with IDUs as with gay men, the infected and affected communities have been brought into partnership with health educators, researchers and policy makers.This paper will review Australia's approach to the prevention of BBVI in IDUs and the effectiveness of current strategies. I will argue that while HIV/AIDS among heterosexual IDUs appears to have been successfully prevented, international experiences of rapidly emerging epidemics demonstrate there is little room for complacency. Moreover, reducing the incidence of hepatitis C and hepatitis B among IDUs remains a major challenge.